Menghidupkan Kembali Indentitas Melayu: Program Pelatihan Bahasa dan Eco-Print bagi Siswa di Pattani Thailand - Kusuma, Menur; Rahayu, Sri (Pendidikan Matematika, FKIP Universitas Mataram, 2025)
The border region between Thailand and Malaysia has long been a conflict-prone area, particularly in Southern Thailand, where demands for independence have arisen due to restrictions on the use of the Malay language and Islamic practices. This study examines the impact of an international community service program conducted through a collaboration between Universiti Muhammadiyah Malaysia (UMAM), Universiti Sains Malaysia (USM), and universities from Indonesia. The program aims to empower the community both culturally and economically by reintroducing the Malay language and providing eco-print training as a sustainable entrepreneurial skill. This research employs a qualitative approach using the Participatory Action Research (PAR) method, involving interviews, direct observations, and Focus Group Discussions (FGD) with students at Pattani Learning School, Pattani. Data were collected to evaluate students' perceptions of Malay language preservation and eco-print training as an entrepreneurial skill. The findings indicate that the eco-print training equips students with new skills that have the potential to support their economic independence. Moreover, the reintroduction of the Malay language was positively received by participants, reinforcing their cultural identity. Students demonstrated a high level of enthusiasm for both aspects of the program, highlighting the importance of culture-based education in enhancing their understanding and appreciation of local heritage. This program demonstrates that cultural and economic empowerment can play a crucial role in language preservation and community well-being. The integration of eco-print training with Malay language revitalization can serve as a sustainable community service model in conflict areas, fostering peace and sustainable development in Southern Thailand.